DOI: 10.17760/d20271420
|View full text |Cite
|
Sign up to set email alerts
|

Exploring online critical inquiry experiences of first year undergraduate nursing students in a northeast American college

Abstract: Developing practitioners who can think critically is a core goal in the nursing discipline. The ability to prioritize information, problem solve, and support decisions with evidence positively correlates with patient quality of care, safety, and outcomes. These skills however are challenging to teach and learn, and research shows many nursing students and new nurses lack proficiency. As programs move online, it is imperative we understand how to better design and teach courses for improved critical inquiry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 129 publications
(327 reference statements)
0
1
0
Order By: Relevance
“…Hospitals and nursing schools neglect workplace violence against nursing interns, which leads to a high prevalence of workplace violence against nursing interns. In an US study, over 50% of nursing interns reported experiencing horizontal violence at least once during a clinical setting (Wallace & Tucker, 2019 ). Cheung et al ( 2019 ) found that 30.6% of nursing interns in Hong Kong reported having received verbal threats, and 16.5% reported having been physically assaulted.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals and nursing schools neglect workplace violence against nursing interns, which leads to a high prevalence of workplace violence against nursing interns. In an US study, over 50% of nursing interns reported experiencing horizontal violence at least once during a clinical setting (Wallace & Tucker, 2019 ). Cheung et al ( 2019 ) found that 30.6% of nursing interns in Hong Kong reported having received verbal threats, and 16.5% reported having been physically assaulted.…”
Section: Introductionmentioning
confidence: 99%